In vitro and in situ assessment of Proanthocyanidin on enamel erosion prevention - Boteon, Ana Paula (2020)
Proanthocyanidin is a natural agent that has been extensively tested in Dentistry in different fields with promising results, including on dental erosion. It has an interesting performance on dental tissues, especially on dentin, in which interacts with collagen matrix, inducing cross-linker formation and improving the dentin mechanical properties. However, as Proanthocyanidin can also act on de-remineralization process as well as interacting with salivary proteins, it might play a role on enamel erosion prevention. Thus, the aim of this thesis was to evaluate the Proanthocianidin on enamel erosion by in vitro and in situ studies, not necessarily in that order. The first study evaluated the effect of Proanthocyanidin applied over acquired enamel pellicle on initial erosion. The acquired pellicle was formed in situ by the placement of intraoral palatal devices in two healthy volunteers for 2 hours. The enamel blocks of each group were treated in vitro: G1: 6.5% proanthocyanidin gel and acquired pellicle formed in situ; G2: only 6.5% proanthocyanidin gel; G3: only acquired pellicle formed in situ; and G4: no intervention. Gels were applied for 1 minute. Then, enamel blocks were immersed in 0.5% citric acid, pH 2.5, for 30 seconds to promote a short erosive challenge. The response variable was the percentage of surface hardness loss was carried out. Data analysis showed that the G1 group showed the lowest value of hardness loss compared to other groups (G2, G3 and G4), which exhibited a greater hardness loss with no significant difference among them. The article 2 evaluated the in vitro effect of Proanthocyanidin on noneroded and eroded enamel compared to fluoride submitted to 5-day erosive cycling. Gels was applied were applied once every day before the first erosive cycling. The enamel erosion was carried out with cola drink for 5 minutes, 3 times per day. The enamel loss determination was performed by profilometry analyses. Results showed that the tested gels were not able to prevent the enamel wear. Finally, the article 3 evaluated the effect of Proanthocyanidin applied over acquired enamel pellicle, but on 5-day erosive cycling. The studied groups were Proanthocyanidin gel on acquired enamel pellicle, only Proanthocyanidin gel and only acquired enamel pellicle. Three volunteers were responsible to the placement of intraoral palatal devices for the acquired pellicle groups. The erosive cycling consisted by immersion of the enamel blocks in the same kind of acid from article 1, but for 2 minutes, 3 times per day. The enamel loss was determined by profilometry analysis. Data analysis suggested that Proanthocyanidin can prevent enamel loss only on acquired pellicle presence.